AKTIVITAS KOMUNIKASI PEMASARAN DINAS PARIWISATA KOTA SURAKARTA DALAM MENINGKATKAN POTENSI KUNJUNGAN WISATA BUDAYA DI KOTA SURAKARTA PASCA PANDEMI TAHUN 2019-2022 MELALUI MEDIA SOSIAL INSTAGRAM - Bunga Sabatani, Clarisa Fanindia; Hindra Hastuti, Nurnawati; Widiyowati, Estu (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
Surakarta City is a cultural tourism city that presents many historical places that have the potential to become tourist sites and one of the cities in Indonesia that is interesting to visit. The presence of various cultural tourism and traditions characterize the city of Surakarta. The purpose of this research is to find out the marketing communication strategy at the Surakarta City Culture and Tourism Office towards the development of cultural tourism to increase tourist visits. This research uses Push Strategy which aims to increase the quantity and quality of tourism products and improve services (Public Relations Strategy in Tourism Promotion, 2018, p. 399). This type of research is descriptive qualitative, determining sources in this study using observation and interview methods. The resource person in this research is one who is engaged in the Tourism Marketing Sub-Coordinator. The results in this study are positive regarding the increase in the number of tourist visit data after the Covid-19 pandemic because it has succeeded in achieving increased data. The conclusion of marketing communication activities carried out by the Surakarta City Culture and Tourism Office on Instagram social media through Influencers and Events can increase cultural tourism visits in Surakarta City. Positive suggestions for marketing communication strategies carried out by the Surakarta City Culture and Tourism Office need to develop IT experts so as to increase creative content so that it can attract potential tourists. Keywords: Surakarta City Culture and Tourism Office, Marketing Communication Strategy, Instagram Social Media